An examination of Oliver's product loyalty framework. Issue 2 (29th April 2016) - Trail, Galen T.; James, Jeffrey D.; Kwon, Hyungil; Anderson, Dean; Robinson, Matthew J.
Abstract : Purpose: – The purpose of this paper is to test Oliver's two-dimension (fortitude and community/social support) product loyalty framework. Design/methodology/approach: – Oliver categorized each of the two dimensions into high and low, creating a two-by-two framework: low fortitude and low-community/social support (Product Superiority group); low fortitude and high-community/social support (Village Envelopment group); high fortitude and low-community/social support (Determined Self-isolation group); high fortitude and high-community/social support (Immersed Self-identity group). The paper uses two samples. The sample from Study 1 was season ticket holders ( n =199) of a West Coast (USA) Major League Baseball team. Results indicated preliminary support for Oliver's four groups and good psychometric properties of the fan community scale and the individual fortitude scale (IFS). Study 2 focussed on attendees ( n =458) at two East Coast (USA) Major League Baseball venues. Findings: – The multivariate GLM indicated significant differences among Oliver's groups, but the variance explained was small on past, current, and future attendance. However, in terms of actual games attended, the Immersed Self-identity group attended between 2.5 and 3 times as many games as the Village Envelopment group over the two years, and more than twice as many games as the Product Superiority group. The groups differed substantially on consumption of product extensions: 22.5 percent of the variance in merchandise purchasing was explained by the grouping, 31.9 percent of broadcast media consumption, and 24.9 percent of print media consumption. In all cases, those in the Immersed Self-identity group consumed significantly more than the Product Superiority and Determined Self-isolation groups. Originality/value: – The paper reveals that sport marketers can focus on the Immersed Self-identity segment as the segment most likely to consume the product, repurchase, and purchase product extensions.